Practices in Physical Education teacher training: Documentary analysis of accreditations in Chile - Hinojosa-Torres, Claudio; Espoz-Lazo, Sebastián; Zavala-Crichton, Juan Pablo; Cañadas Martin, Laura; Yáñez-Sepúlveda, Rodrigo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
In Chile, accreditation of pedagogy programs is crucial to ensure quality in teacher training, according to Law 20.129. This qualitative documentary study reviewed 29 accreditation resolutions of Physical Education Pedagogy programs, using content analysis with Atlas.ti 24. The findings reveal that: a) practice is essential in teacher training; b) the quality and quantity of practice centers are key to achieve training objectives; and c) collaboration between universities and the school system raises the quality of educational practices.